PERILAKU DUNIA USAHA/INDUSTRI PADA PROGRAM PENDIDIKAN SISTEM GANDA SEKOLAH MENENGAH KEJURUAN DALAM POLA MAGANG SATU TAHUN DI KOTA SEMARANG - -, Sudarman (Jurnal Pendidikan Teknik Mesin, 2005)
The aim of this research is to know the behaviour of industialist in UANAS (National Final Examination) score selection, interview test and at productive skill practice and also supports of UANAS score and interview score toward the achievement of productive skill practice. This research was carried out in SMK N 11 and printing industry in Semarang city in 2004/2005 school years. Sample subyect taken by 50 students Data were taken with documentation, questionair, score card and they are analized with: descriptive statistic, multiple regression and commonality. This research concluded that: (1) industrialist behaviour in the National Final Examination score selection is enough, in the interview test is enough and productive skill practice is good. (2) the high and low score of National Final Examination is balance, most of interview test score is high, most of productive skill practice achievement is high, (3) combination that National Final Examination selection score and interview test score has support 66,9 % toward productive skill practice achievement, (4a) interview test score has support 46% toward productive skill practice (4b) achievement and National Final Examination score by self supportingly doesn’t have support toward productive skill practice achievement.